Agreement towards task sharing among gynecologist and general practitioners in north-eastern Germany. (30th September 2020) - Schuster, A; Grittner, U; Dini, L
Abstract: Background: In Germany, a higher life expectancy of women coincides with shortages of health professionals. Besides gynecologists (Gyns), the main providers of ambulatory healthcare for women 50+ are general practitioners (GPs), which do not provide gynecological care. However, GPs and Gyns willingness share tasks has not yet been analysed systematically. The aim of this research project is to explore approval among and consent between GPs and Gyns for task sharing in women 50+. Methods: In a quantitative postal survey (March-May 2018), a random sample of 66% of all GPs (n = 3, 514) and all Gyns (n = 1, 031) in the three German states was interviewed. The response rate was 25.5% for GPs and 51.2% for Gyns. The approval for task sharing (yes/no) was collected for 21 medical consultation themes (83 sub items) regarding women's health and general health of women 50+. For each sub item, the approval rates among and consent between the professional groups was calculated and sub items were group into medically coherent modules for interprofessional care. Multivariable regressions were calculated in order to explore the association of professional group with the medically coherent modules adjusted for covariates. Results: In both professional groups, highest approval was reached for shared care of urinary incontinence, vaginal complaints and recurrent urinary tract infections. High approval and consent was present only for the sub items counselling for sexual health (GP = 52.30%, Gyn=48.91%) and colorectal cancer screening (GP = 48.66%, Gyn=44.70%). Approval was higher for counselling as compared to diagnostics and therapy. Cancer related task went along with low approval rates in both professional groups. Approval towards task sharing was higher among Gyns for all modules except for cancer screening. Conclusions: The analysis identified single tasks for sharing in both groups and allows setting priorities through the classification according to approval and consent. Key messages: Task sharing among GPs and Gyn could be an opportune answer to improve access to care of women 50+. Knowledge on GPs and Gyns attitudes towards task sharing can serve as common empiric ground for meaningful dialogues between research, policy and practice.